A new two-fluid model for flow rate measurement of annular flow in horizontal pipe. (15th June 2022) - Wang, Mi; Zheng, Dandan; Xu, Ying
Highlights: A modeling measurement system is designed. A two-fluid model is proposed for flow rate measurement of horizontal annular flow. The predicted and measured pressure drop are compared to verify the two-fluid model. A flow rate measurement system including multimodal ultrasonic sensors is set up. Flow rates are obtained by the flow rate measurement system with two-fluid model. Abstract: Non-separation measurement is a research difficulty and hotspot in multiphase flow. In this paper, the multimodal ultrasonic sensors and differential pressure transmitter combined with two-fluid model are used to measure the wet gas flow rates under non-separation state. Firstly, a modeling measurement system is built. The liquid film thickness and pressure drop are obtained by using ultrasonic sensor and differential pressure transmitter. Based on the steady-state one-dimensional two-fluid model and the limitations of existing models, a new prediction model is proposed. Comparing the pressure drop data obtained by new two-fluid model with the experimental data, the errors are within ±30%. Then, wet gas flow rates measurement system is constructed. The liquid film thickness and gas velocity are measured by using multimodal ultrasonic sensors. Combined this new two-fluid model, the wet gas flow rates are obtained. The measurement errors of gas and liquid flow rate are within ±10% and ±15%.